2017
DOI: 10.5194/acp-17-11707-2017
|View full text |Cite
|
Sign up to set email alerts
|

Biomass burning at Cape Grim: exploring photochemistry using multi-scale modelling

Abstract: Abstract. We have tested the ability of a high-resolution chemical transport model (CTM) to reproduce biomass burning (BB) plume strikes and ozone (O 3 ) enhancements observed at Cape Grim in Tasmania, Australia, from the Robbins Island fire. The CTM has also been used to explore the contribution of near-field BB emissions and background sources to O 3 observations under conditions of complex meteorology. Using atmospheric observations, we have tested model sensitivity to meteorology, BB emission factors (EFs)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The C-CTM is a modelling framework which simulates the emissions, transport and wet and dry deposition of chemical species in the atmosphere. Previously, the C-CTM has successfully been used in several air quality applications, including investigating smoke from biomass burning [33], shipping emissions [34] and biogenic emissions [35,36].…”
Section: Regional Air Quality Modelling Using C-ctmmentioning
confidence: 99%
“…The C-CTM is a modelling framework which simulates the emissions, transport and wet and dry deposition of chemical species in the atmosphere. Previously, the C-CTM has successfully been used in several air quality applications, including investigating smoke from biomass burning [33], shipping emissions [34] and biogenic emissions [35,36].…”
Section: Regional Air Quality Modelling Using C-ctmmentioning
confidence: 99%
“…Given the complexity and variability in biomass burning scenarios and the use of emission factors (EFs, in units of kilograms of VOC emitted per kilogram fuel burnt) to inform air quality models, this can lead to issues in effectively constraining emissions. For example, Lawson et al (2017) reported a strongly non-linear response in simulated ozone (O 3 ) when varying biomass burning (BB) EFs, showing the resulting sensitivity from chemical transport models (CTMs). This sparseness of measurements leads to the use of North American EFs (such as those from Burling et al, 2011 to inform CTMs, simulating emissions of geographically separate biomes.…”
Section: Introductionmentioning
confidence: 99%
“…While smoke has the potential to significantly influence urban O 3 mixing ratios, actual impacts are difficult to determine and highly variable O 3 impacts have been observed. ,, Simulating these O 3 impacts with photochemical models has proven challenging for several reasons, including incomplete emissions data, high sensitivity to meteorology, and difficulty capturing heterogeneous chemistry . Further, traditional grid models do not simulate smoke plume photochemistry well, especially as it relates to downwind O 3 . ,,, While Lagrangian parcel models have had some success, more work is needed.…”
Section: Introductionmentioning
confidence: 99%